Análisis de la desigualdad de largo plazo en Bolivia 1976-2012 - Luis Castro; Gustavo Zárate Taborga; Valeria Salinas Maceda (Institute for Advanced Development Studies (INESAD), 2018)
– Inequality in Bolivia is normally measured through income. However, the construction of a socio-economic index (ISE), using the four available censuses 1976, 1992, 2001 and 2012, permits to analyze inequality in long-term as well as under a multidimensional approach. Through the application of an inter-temporal decomposition approach, we can identify relevant variables such as ethnicity and gender (of the head of household) both in structure and in composition of the ISE change over time at the quantile level.
Keywords: D63; I32; O15; 330; inequality; gender; ethnicity; variance decomposition